Synthesis and Characterisation of Biolubricants Castor Oil (Ricinus communis L.) Using a Homogeneous Catalyst for Hydraulic Engine Applications - Suherman, Suherman; Muktar, Muharnif; Kurniawan, Rendy; Abdullah, Ilmi; Mawardi (Mechanical Engineering Department - Semarang State Polytechnic, 2025)
Lubricants are essential products that help reduce surface friction and improve machine efficiency. Lubricating oil consists of 90% base oil and 10% additives. Due to the presence of low molecular weight compounds, mineral-based lubricants exhibit a lower flash point and are not biodegradable, unlike natural oils with equivalent viscosity. Currently, mineral-based lubricants still dominate the global market, yet their environmental drawbacks and reliance on depleting petroleum resources have raised growing concerns. Although several studies have reported the potential of vegetable oils as biolubricants, challenges remain in terms of oxidative stability, viscosity control, and production scalability, which limit their widespread industrial application. The high dependence of the industrial and automotive sectors on lubricants, coupled with the depletion of petroleum reserves, drives the need to seek sustainable alternatives to support sustainable green economic development. This study aims to produce biolubricants from castor oil (Ricinus communis L.) using NaOH catalyst through an esterification method. Esterification was carried out by mixing the oil with alcohol in a molar ratio into a 250 ml three-neck flask, then heating it to 180 °C for 4 hours with 1–2% NaOH catalyst and a methanol-to-oil molar ratio of 1:4. The results showed that the highest values of kinematic viscosity, viscosity index (VI), and density were 28.9 mm²/s, 90.3, and 884.9 kg/m³, respectively. The optimum biolubricant yield was obtained with 2% catalyst (80%). The produced biolubricant met the ISO VG 32 standard, which is widely applied in hydraulic oils, for turning, drilling, and sawing processes. These findings highlight that castor oil-based biolubricants can serve as a sustainable alternative to petroleum-based lubricants; however, further research on long-term stability, wear resistance, and large-scale production remains necessary to bridge the gap towards industrial adoption.